Construção-de-sentido em organizações: análise para contribuição aos estudos brasileiros - Prado Filho, João da Motta (2005)
This dissertation aimed at analyzing how is currently theoretically textualized the thematic of sense construction and sense making, while phenomenon and process, within organizations. In short, it deepens into the ‘sense making’ category, so it can be better assessed and studied within organizational setting. How could it be processed and under which terms analyzed? How are these studies in Brazil and worldwide? Amidst questions like these, the author elected to perform an explanatory independent bibliographic research, to strength the database that could highlight the state-of-art of this sensemaking category. The diversified range of study sources and the cultural differences between Anglo-American and Brazilian patterns recommended the usage of a transcultural sensibility for understanding issues in Brazil. Analyses were undertaken in connection with phenomenon and process as regarding to sense making, as well a brief review of current usages of sense making, sense-making and sensemaking in Anglo-American academic literature. Karl Weick’s Sensemaking in organizations (1995) work was referred with his set of seven properties approach. It is obvious the entanglement of the subject with themes from philosophy, sociology, psychology, politics, economics, ontology, phenomenology, among other areas. The complexity starts with the explanation of term “construção-de-sentido”, a neologism by the author used for sensemaking (while category designated for deeper appreciation in this study), between quotation marks and hyphenated, distinguished among construção de sentido e construção do sentido. In search to furthering the understanding, the sense concept is emerged, paralleled with mean and meaning. An emphasis is placed to sense in its straightforward line to relationship, to communication, and with the possibilities in relationships within organizational life. Links are made between sensemaking and strategic management, learning organizations, knowledge management, organizational theory, and organizational behavior, the later being elected for shelter of the category, despite proven its irrelevant presence it this context. The problematic is tied with abundant controversial and paradoxal situations within organizational contexts, lessened involvement of collaborators with organizational goals, and the disinterest of managers for complex aspects of human behavioral knowledge, the basic problem being the frequent human relational incoherence amidst the component parts of an organizational whole. This research aims at contributing to the discussion of the theme inside academy in Brazil, currently not sufficiently exploited, far way from general public and mangers. In addition, intends to amplify the conditions for empirical researches, diffuse e deepen the knowledge, and favor the vision of “manage with the sense” and administrate with sense consciousness the managerial processes. The approach of the seven characteristics compiled by Weick supports the discussion of sensemaking in organizations and is linked to HR Strategic and Technological Management, research line of this theoretical investigation. In the final considerations, the naturalness of human cognitive process is accentuated, and questioned the expectations whether the phenomenon-process analyzed can be intentionally provoked, with social consciousness of social construction, and as a factor capable of detracting organizational ambiguities. Last, suggestions for empirical approaches are given, taking into account advantages and needs of multidisciplinary interactions, distinguishing philosophy, psychology, and sociology.